Perception of extreme hot weather and the corresponding adaptations among older adults and service providers-A qualitative study in Hong Kong - Eric T. C. Lai; Eric T. C. Lai; Pui Hing Chau; Ken Cheung; Michelle Kwan; Michelle Kwan; Kevin Lau; Jean Woo; Jean Woo; Jean Woo (Frontiers Media S.A., 2023)
BackgroundExtreme hot weather events are happening with increasing frequency, intensity and duration in Hong Kong. Heat stress is related to higher risk of mortality and morbidity, with older adults being particularly vulnerable. It is not clear whether and how the older adults perceive the increasingly hot weather as a health threat, and whether community service providers are aware and prepared for such future climate scenario.MethodsWe conducted semi-structure interviews with 46 older adults, 18 staff members of community service providers and two district councilors of Tai Po, a north-eastern residential district of Hong Kong. Transcribed data were analyzed using thematic analysis until data saturation was reached.ResultsIt was agreed upon among the older adult participants that the weather in recent years has become increasingly hot and this led to some health and social problems for them, although some participants perceived that hot weather did not have any impact in their daily lives and they were not vulnerable. The community service providers and district councilors reported that there is a lack of relevant services in the community to support the older adults in hot weather; and there is generally a lack of public education regarding the heat-health issue.ConclusionsHeatwaves are affecting older adults' health in Hong Kong. Yet, discussions and education effort regarding the heat-health issue in the public domain remain scarce. Multilateral efforts are urgently needed to co-create a heat action plan to improve community awareness and resilience.